Analysis of Unreliable Narration in Edgar Allan Poe’s The Tell-Tale Heart - Wang, Ni (Pacific International Journal, 2022)
Edgar Allan Poe was a 19th century American poet, novelist and literary critic. His novel is recognized as the pinnacle of short gothic fiction, a unique existence in any era. The Tell-Tale Heart is a typical Gothic mystery novel of Edgar Allan Poe. The novel tells the process of a crazy young man killing an old man and the psychological changes during the process from a first-person perspective. Much researches had done at home and abroad about The Tell-Tale Heart, mainly around the narrative aesthetics, narrative style and the gothic style, etc., however, few researches focus on reliable narrative, this paper through the study of unreliable narration in The Tell-Tale Heart, let the reader get a better understand of his work The Tell-Tale Heart and Poe’s works.